'We are not Kenyans': extra-judicial killings, manhood and citizenship in Mathare, a Nairobi ghetto. Issue 4 (3rd July 2016) - van Stapele, Naomi
Abstract: This article focuses on the systematic police killings of young, male crime suspects by local police officers in Mathare since 2002. It explores the relationship between executions of young ghetto men by police and notions of citizenship. It firstexmaines the impact of such killings on positions of manhood among these men and the different roles of 'gangs' in popular processes of becoming men. My aim is to move away from the current association of young ghetto men with violence and ethnic politics—i.e. as 'thugs for hire'. One of my main discoveries was that work and manhood are at least as important to grasp processes of group formation among them. After this, the article delves into the question of how to understand the narratives that legitimise and perpetuate this particular form of state violence. It concludes by discussing how processes of subjectivation that constitute, and are constituted by, the dominant discourse on citizenship produce positions of non-citizenship ascribed to ghetto residents, and in particular to young ghetto men.